Modelling vector-borne and other parasitic diseases. Proceedings of a joint ILRAD/FAO workshop - International Laboratory for Research on Animal Diseases (Food and Agriculture Organization of the United Nations, 1994)
Session one of this Report highlights ILRAD's research programs and the modelling needs of ILRAD and FAO. Session two deals with vector and helminth population dynamics with partic. ref. to ticks, tsetse and helminth. Parasite transmission and host parasite interaction are discussed in sessions three and four respectively. These two sessions deal with Theileria, trypanosomes and Leishmania. Parasite variations and polymorphism is the topic of session five. Session six discusses the effect of disease control programs and session seven reviews modelling systems. The last two sessions deal with the application of modelling, and collection, collation, analysis and dissemination of data on vector-borne and other parasitic diseases.